Maqam Muraqabah ; Perspektif Imam Abu Hasan Asy Syadzili dalam Kitab Risalah Al-Amin - Maya Rahmadani; Idrus Alkaf; Erika Septiana (CV. ITTC INDONESIA, 2024)
Muraqabah is a person's belief that Allah SWT is watching, seeing, listening and knowing every moment, every breath, every blink of an eye. However, many people today do not realize that every action is under the supervision of Allah. Therefore, it is important to make someone aware of the need to apply this muraqabah in everyday life to strengthen their faith by instilling good qualities. The study aims to determine the maqam of muraqabah in the world of Sufism from the perspective of Imam Abu Hasan Asy Syadzili in the book Risalah al-amin and to find out the implementation of muraqabah in life can improve the quality of worship and get closer to Allah. The method used is a qualitative approach (Library Research) with a content analysis model, through a Sufism approach. Conclusion Muraqabah according to Sheikh Abu Hasan Asy Syadzili in the book Risalah al-Amin is a deep spiritual concept in Sufism. Muraqabah literally means “supervision or observation”, but in a spiritual context it refers to one's awareness and continuous monitoring of God's presence in every aspect of one's life. Implementing muraqabah can help individuals improve the quality of worship and get closer to Allah SWT. Therefore, muraqabah can be applied in everyday life through several steps, such as: (1). Be loyal and devoted to God with true sincerity. (2). Amar ma'ruf nahi evil through repentance and continuous reflection. (3). Gratitude is manifested in good thoughts, words and deeds. (4). Keep your heart and all parts of your body always istiqamah. (5). Be patient in facing life's trials and disasters. (6). Patience to carry out God's commands without